PENGEMBANGAN MEDIA PEMBELAJARAN MOBILE LEARNING BERBASIS ANDROID MATA PELAJARAN IPA UNTUK SISWA SMP - Nurwahyuningsih Ibrahim; Ishartiwi Ishartiwi (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2017)
This study aims to (1) produce learning media based on android mobile learning (2) to know the level of feasibility of learning media according to material experts, media experts, and users, (3) to know the effectiveness of learning media to improve the learning outcomes of junior high school students. This development study follows the steps developed by Alessi and Trollip consisting of three stages: planning, designing and development. Initial product validated by media expert and material expert then revised. The next stage is a small group beta test carried out to six prospective users, and tested to 32 users. Furthermore sumative test against 32 students. The results showed that (1) android-based mobile learning products packaged in android package format (apk) using helios eclips software. (2) mobile learning product is considered feasible as a learning media based on the assessment of media experts 3,8 and material experts 4.3 with the category of "very good". (3) the effectiveness of the product is evidenced by the increase of learning outcomes to reach the average score of pretest score 65.46 and posttest of 79.53